2009
DOI: 10.1097/jom.0b013e3181a83567
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Work Productivity With a Mental Health Self-Report Measure

Abstract: The SR can be used to estimate work productivity using tools like the Productivity Calculator. Specific relationships among measures and suggestions for future research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…Examples of SR items are ''I feel stressed at work,'' and ''I am not working as well as I used to.' ' Trotter et al (2009) reported that SR provides a good estimate of work productivity.…”
Section: Eap Counseling Outcomes 129mentioning
confidence: 98%
See 1 more Smart Citation
“…Examples of SR items are ''I feel stressed at work,'' and ''I am not working as well as I used to.' ' Trotter et al (2009) reported that SR provides a good estimate of work productivity.…”
Section: Eap Counseling Outcomes 129mentioning
confidence: 98%
“…The Outcome Questionnaire-45.2 (OQ) had been incorporated into this EAP's intake and case-closing procedures four years prior to the start of this quality improvement review for a number of reasons. It is widely used in counseling settings, and there is an extensive literature documenting its validity, reliability, and comparability across populations (Lambert et al, 2004;Minami et al, 2009;Trotter et al, 2009). It was validated in part on a sample of 504 EAP clients, and normative data for this EAP sample (as well as for several other sample groups) are available for comparison purposes in the OQ manual.…”
mentioning
confidence: 99%
“…Withdrawal behaviours can be psychological or physical (Trotter et al . ). Psychological withdrawal behaviours include presenteeism and burnout.…”
Section: Methodsmentioning
confidence: 97%
“…Rather, the health care environment that can often be understaffed and stressful can be accountable and responsible for destructive behaviours. Withdrawal behaviours can be psychological or physical (Trotter et al 2009). Psychological withdrawal behaviours include presenteeism and burnout.…”
Section: Destructive Behavioursmentioning
confidence: 99%
“…Lambert et al (2004), using the Outcome Questionnaire-45.2 (OQ), found that a sizeable percentage of EAP clients showed significant improvement over the course of brief treatment. More recently, Trotter et al (2009) indicated that the OQ Social Role Scale (SR) may provide reliable estimates of two issues very relevant to EAP-based counseling: presenteeism and work activity impairment.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%